The great god Pan reborn in Renaissance Florence - McLellan, Dugald (Spunti e Ricerche, 2016)
Each of the many interpretations of the enigmatic composition known as the School of Pan has merit though there is no attempt to test them in this paper. The present hypotheses do not set out to supplant such interpretations but rather to add further layers of meaning to a work that was clearly intended to be as polysemous and as mysterious as the God it celebrates. Three readings of the work are proposed which might fall under the headings of literal, metaphorical and allegorical.